Structural Studies of Salmonella typhimurium ArnB (PmrH) Aminotransferase : A 4-Amino-4-Deoxy-L-Arabinose Lipopolysaccharide-Modifying Enzyme - Noland, Brian W.; Newman, Janet M.; Hendle, Jörg; Badger, John; Christopher, Jon A.; Tresser, Jason; Buchanan, Michelle D.; Wright, Tobi A.; Rutter, Marc E.; Sanderson, Wendy E.; Müller-Dieckmann, Hans-Joachim; Gajiwala, Ketan S.; et al. (Structure (London), 2002)
Lipid A modification with 4-amino-4-deoxy-L-arabinose confers on certain pathogenic bacteria, such as Salmonella, resistance to cationic antimicrobial peptides, including those derived from the innate immune system. ArnB catalysis of amino group transfer from glutamic acid to the 4″-position of a UDP-linked ketopyranose molecule to form UDP-4-amino-4-deoxy-L-arabinose represents a key step in the lipid A modification pathway. Structural and functional studies of the ArnB aminotransferase were undertaken by combining X-ray crystallography with biochemical analyses. High-resolution crystal structures were solved for two native forms and one covalently inhibited form of S. typhimurium ArnB. These structures permitted identification of key residues involved in substrate binding and catalysis, including a rarely observed nonprolyl cis peptide bond in the active site.